ANALISIS FITOKIMIA DAN PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL DAUN KETAPANG KENCANA (Terminalia mantaly) SECARA SPEKTROFOTOMETRI UV-VIS - Veronika Puspita Kumalasari; Zaenal Fanani; Emma Jayanti Besan (Nusantara Hasana Journal, 2025)
The Ketapang Kencana plant (Terminalia mantaly) is one of the plants with potential as a source of bioactive compounds. Traditionally, various parts of this plant, such as the leaves, stems, and root bark, have been used in several countries to treat diseases such as diabetes, dysentery, and malaria. This study aims to identify the active compounds present in the ethanol extract of Ketapang Kencana leaves and to determine the total flavonoid content of the ethanol extract of Ketapang Kencana leaves. The extraction was carried out using the maceration method with 70% ethanol as the solvent. Phytochemical screening of the ethanol extract of Ketapang Kencana leaves was conducted using specific chemical reagents. The results of the phytochemical screening showed that the ethanol extract of Ketapang Kencana leaves contains alkaloids, flavonoids, saponins, tannins, and triterpenoids. The total flavonoid content of the ethanol extract of Ketapang Kencana leaves, determined using the colorimetric method with UV-Vis spectrophotometry and quercetin as the standard, was found to be 26.847 mgQE/g extract on average.